Research on high efficiency coagulation process of poly-silicic-ferric by response surface methodology. Issue 5 (May 2019) - Gao, D; Fu, Y
Abstract: The Box-Behnken response surface methodology was used to optimize the coagulation and sedimentation processes using poly-silicic-ferric (PSF) as coagulant. The quadratic regression equation with the dosage, flocculation time and precipitation time as the independent variables and the turbidity removal rate as the response value was established to determine the optimal process conditions of the PSF. The response surface results showed that the dosage of the agent, the flocculation time, the precipitation time and the interaction between them all had significant effects on the coagulation properties of the PSF. The optimal turbidity removal rate of PSF was 99.2% when the dosage of the agent, the flocculation time and the precipitation time were 7.2 mg/L, 5 min and 3 min, respectively. In addition, the predicted values were in good agreement with the measured values, and the model had high credibility. This indicated that PSF can coagulate and precipitate the impurity particles in a short time, which can shorten the time of the coagulation and sedimentation processes.